Perspectives in Interdisciplinary and Integrative Studies - Schovanec, Lawrence, 1952-; Tanner, Marcus N.; Munoz, Juan Sanchez, 1967-; Hughes, Patrick C. (Book collections on Project MUSE., 2015)
"Collection examining integrative and interdisciplinary scholarship, focusing on the integrative knowledge, theory, methods, and program development and assessment in education"--Provided by publisher.